2022
DOI: 10.2172/1899557
|View full text |Cite
|
Sign up to set email alerts
|

Radioactive Waste Sludge Washing and Demonstration of the Nitric-Glycolic Acid Flowsheet for Sludge Batch 10 Qualification

Abstract: For each sludge batch that is processed in the Defense Waste Processing Facility (DWPF), the Savannah River National Laboratory (SRNL) performs qualification testing to demonstrate that the sludge batch (SB) is processible. During processing of SB9, DWPF will be transitioning from the Nitric-Formic Acid (NFA) flowsheet to the Nitric-Glycolic Acid (NGA) flowsheet. Thus, the qualification of SB10 was requested to only be performed using the NGA flowsheet.In order to qualify the batch for the NGA flowsheet, Sludg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…It is unknown whether other interactions may occur with antifoam components, but any such interactions with Gd or other metals in the system had not been observed to impact the effectiveness of antifoam during SB10 qualification testing. 34 Due to the lack of a study specifically designed to elucidate gadolinium interactions, it has not been determined whether there is a glycolic acid and gadolinium interaction beyond what is expected from the lowering of the pH. Studies have shown that the gadolinium goes from partitioning completely in the solid phase in the basic SRAT Receipt to partitioning almost fully (≥80%) into the liquid phase in the acidic DWPF CPC products that have received excess acid addition.…”
Section: Srnl-sti-2022-00502mentioning
confidence: 99%
See 2 more Smart Citations
“…It is unknown whether other interactions may occur with antifoam components, but any such interactions with Gd or other metals in the system had not been observed to impact the effectiveness of antifoam during SB10 qualification testing. 34 Due to the lack of a study specifically designed to elucidate gadolinium interactions, it has not been determined whether there is a glycolic acid and gadolinium interaction beyond what is expected from the lowering of the pH. Studies have shown that the gadolinium goes from partitioning completely in the solid phase in the basic SRAT Receipt to partitioning almost fully (≥80%) into the liquid phase in the acidic DWPF CPC products that have received excess acid addition.…”
Section: Srnl-sti-2022-00502mentioning
confidence: 99%
“…Increases in metal solubilities after moderate to high acid addition (approximately ≥100% Koopman minimum acid (KMA)) in the NGA flowsheet can lead to higher supernate densities and soluble solids in the SRAT and SME Products. 34,[37][38] This dissolution of metals is part of the NGA flowsheet and does not have significant adverse chemical or physical impacts on the remainder of the DWPF process. 39 If there is a foamover that introduces SRAT or Slurry Mix Evaporator (SME) material containing glycolate into the SME condensate tank, the glycolate (and glycolate complexes) will be destroyed in the RCT by sodium permanganate added to the RCT prior to transfer to Tank 22.…”
Section: Srnl-sti-2022-00502mentioning
confidence: 99%
See 1 more Smart Citation
“…Savannah River National Laboratory (SRNL) completed a small-scale demonstration of the Defense Waste Processing Facility (DWPF) Chemical Process Cell (CPC) utilizing the nitric-glycolic acid (NGA) flowsheet to support Sludge Batch 10 (SB10) qualification. [1][2][3][4][5] The demonstration utilized a Tank 51 slurry sample washed by SRNL 6,7 . During washing, material from H-Canyon Tanks 16.3 and 16.4 was also added.…”
Section: Introductionmentioning
confidence: 99%